Case report: Traumatic hemorrhagic cervical myelopathy in a dog - Santifort, Koen M.; Carrera, Ines; Platt, Simon (Frontiers in Veterinary Science, 2023)
A 1.5-year-old female entire French bulldog was referred for neurological evaluation, further diagnostic tests, and treatment 24 hours after a road traffic accident. Initial emergency treatment, diagnostic tests, and stabilization had been performed by the referring veterinarian. Neurological examination revealed severe spastic non-ambulatory tetraparesis and was consistent with a C1-5 myelopathy. A magnetic resonance imaging (MRI) study revealed an irregular to elongated ovoid intramedullary lesion centered over the body of C2. The lesion showed marked signal heterogeneity with a central T2W and T2* hyperintense region, surrounded by a hypointense rim on both sequences. The lesion appeared heterogeneously T1W hypointense. The lesion was asymmetric (right-sided), affecting both white and grey matter. The C2-3 intervertebral disc appeared moderately degenerate with a Pfirrmann grade of 3. No evidence of vertebral fracture or luxation was found on radiographs or MRI of the vertebral column. Additional soft tissue abnormalities in the area of the right brachial plexus were suggestive of brachial plexus and muscle injury. A diagnosis of traumatic hemorrhagic myelopathy at the level of C2 and concurrent brachial plexus injury was formed. Conservative treatment was elected and consisted of physiotherapy, bladder care with an indwelling urinary catheter, repeated IV methadone based on pain scoring (0.2 mg/kg), oral meloxicam 0.1 mg/kg q24h and oral gabapentin 10 mg/kg q8h. The dog was discharged after four days, with an indwelling urinary catheter and oral medication as described. The catheter was replaced two times by the referring veterinarian and finally removed after 10 days. Thereafter, voluntary urination was seen. During the 2 months after the road traffic accident, slow recovery of motor function was seen. The right thoracic limb recovery progressed more slowly than the left limb, also showing some lower motor neuron signs during follow-up. This was judged to be consistent with a right-sided brachial plexus injury. The dog was reported ambulatory with mild residual ataxia and residual monoparesis of the right thoracic limb at the last follow-up three months post-injury. This case report highlights the MRI-based diagnosis of traumatic hemorrhagic myelopathy in a dog. A fair short-term outcome was achieved with conservative treatment in this case.